2020
DOI: 10.3390/rs12132097
|View full text |Cite
|
Sign up to set email alerts
|

Cirrus Cloud Identification from Airborne Far-Infrared and Mid-Infrared Spectra

Abstract: Airborne interferometric data, obtained from the Cirrus Coupled Cloud-Radiation Experiment (CIRCCREX) and from the PiknMix-F field campaign, are used to test the ability of a machine learning cloud identification and classification algorithm (CIC). Data comprise a set of spectral radiances measured by the Tropospheric Airborne Fourier Transform Spectrometer (TAFTS) and the Airborne Research Interferometer Evaluation System (ARIES). Co-located measurements of the two sensors allow observations of the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For example, several studies showed that a large fraction of the OLR energy lies in the FIR region (Bellisario et al., 2019; Chen et al., 2014; Harries et al., 2008; X. Huang et al., 2008; Martinazzo et al., 2021; Turner & Mlawer, 2010). Moreover, as the OLR in FIR is especially sensitive to atmospheric water vapor and clouds (e.g., cirrus), investigations and observations in FIR could potentially improve the retrieval of their information (Blanchet et al., 2011; Clough et al., 1992; Cox et al., 2015; Delamere et al., 2010; Harries et al., 2008; Libois & Blanchet, 2017; Maestri & Rizzi, 2003; Magurno et al., 2020; Palchetti et al., 2015, 2016; Sinha & Harries, 1995). To give a few examples, Clough et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies showed that a large fraction of the OLR energy lies in the FIR region (Bellisario et al., 2019; Chen et al., 2014; Harries et al., 2008; X. Huang et al., 2008; Martinazzo et al., 2021; Turner & Mlawer, 2010). Moreover, as the OLR in FIR is especially sensitive to atmospheric water vapor and clouds (e.g., cirrus), investigations and observations in FIR could potentially improve the retrieval of their information (Blanchet et al., 2011; Clough et al., 1992; Cox et al., 2015; Delamere et al., 2010; Harries et al., 2008; Libois & Blanchet, 2017; Maestri & Rizzi, 2003; Magurno et al., 2020; Palchetti et al., 2015, 2016; Sinha & Harries, 1995). To give a few examples, Clough et al.…”
Section: Introductionmentioning
confidence: 99%
“…The results fulfill the high requirements of climatologists with a mean bias of −0.15% and a bias-corrected root-mean-square deviation of 7% against SYNOP observations (Bojanowski et al 2018). Cloud classification is significantly improved by machine learning algorithms with classification accuracies of 95% and more (e.g., Chen et al 2018;Ozkan et al 2018;Reguiegue and Chouireb 2018;Gao et al 2019;Jeppesen et al 2019;Li et al 2019;Magurno et al 2020;Mahajan and Fataniya 2020;Meraner et al 2020;Sun et al 2020;Dubovik et al 2021).…”
Section: Appendix C: Cloud Observations From Spacementioning
confidence: 99%
“…louds are omnipresent in the Earth atmosphere, where they are significant actors in weather, hydrology, climate, air chemistry, and several practical applications such as atmospheric aviation hazards and solar energy use (e.g., Bonkaney et al 2017;Romano 2020;Mahajan and Fataniya 2020;Yuchechen et al 2020;Prata 2020). With a global annual mean cloud cover of ≈66% (Zhang et al 2004;Wang et al 2020), clouds strongly affect the radiation budget of the Earth both in the solar and thermal spectral ranges, thus governing the state and forcing of Earth's climate (L. Dai et al 2019;Magurno et al 2020;Romano 2020;Wang et al 2020;Dubovik et al 2021). It is generally accepted that clouds are the most uncertain determinants in model estimates of global warming (e.g., Dai et al 2019;Romano 2020).…”
mentioning
confidence: 99%
“…The far-infrared (FIR) spectral band is essential to the radiation spectrum, ranging from about 100 to 667 cm −1 (15-100 µm) spectra [19]. The equivalent blackbody temperature of the Earth is 255 K, whose peak energy occurs at about 500 cm −1 in the FIR [20].…”
Section: Introductionmentioning
confidence: 99%